1975
DOI: 10.1139/z75-064
|View full text |Cite
|
Sign up to set email alerts
|

Sexual differences in the growth of Pteronarcys californica Newport and Pteronarcella badia (Hagen) (Plecoptera)

Abstract: Two species of Plecoptera, Pteronarcys californica Newport and Pteronarcella badia (Hagen), were collected seasonally from a single site in the Provo River, Utah. Body weights of the living animals were used to distinguish four size classes in each sex of Pteronarcys californica, and one size class for each sex of Pteronarcella badia. Ovaries, fat bodies, and guts were dissected from Pteronarcys californica. Growth of whole animals and of the organs are discussed with regard to life cycle, sexual development, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…At the High site, the four modes are consistent with a 5 year life cycle comprising an *1 year embryonic diapause followed by 4 years of larval development. Similar developmental patterns have been reported for P. californica in Rio Canejos, Colorado (DeWalt and Stewart 1995) and the Provo river, Utah (Branham and Hathaway 1975), including a longer life cycle (5 year) was reported for P. californica in the Crowsnest river, Alberta, Canada (Townsend and Pritchard 1998). The longer lifespan in the Crowsnest river might be explained by lower temperatures at the more northern latitudes (Tauber et al 1986), and lower temperatures may also explain the longer life cycle at our High site.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…At the High site, the four modes are consistent with a 5 year life cycle comprising an *1 year embryonic diapause followed by 4 years of larval development. Similar developmental patterns have been reported for P. californica in Rio Canejos, Colorado (DeWalt and Stewart 1995) and the Provo river, Utah (Branham and Hathaway 1975), including a longer life cycle (5 year) was reported for P. californica in the Crowsnest river, Alberta, Canada (Townsend and Pritchard 1998). The longer lifespan in the Crowsnest river might be explained by lower temperatures at the more northern latitudes (Tauber et al 1986), and lower temperatures may also explain the longer life cycle at our High site.…”
Section: Discussionsupporting
confidence: 83%
“…Hence, the duration of the life cycle is approximately 5 years in Alberta. In the Provo river, Utah, a four-year life cycle was estimated for P. californica (Branham and Hathaway 1975). DeWalt and Stewart (1995) also estimated a four-year life cycle in the Rio Conejos, Colorado.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the major part of food reserves is stored in the perivisceral fat bodies of the abdomen (Zwick 1980, Chapman 1998. In fact, it has been pointed out that the adipose bodies in stoneflies seem to reach the maximum expansion at the end of the nymphal growth, although in those species in which eggs mature prior to emergence, the adipose bodies tend to decrease when this occurs (Branham andHarthaway 1975, Zwick 1980). In relation to this, it could be hypothesized the existence of an allometric growth of this body region at the end of the nymphal development.…”
Section: -Amentioning
confidence: 99%
“…In the larvae, there is a characteristic mid-ventral notch on the female eighth segment (subgenital plate) that permits sexing. Branham and Hathaway (1975) state that knowing the sex of larvae is important for physiological and bioassay studies, so we examined small larvae to determine the minimum size where this character is present.…”
Section: ) Howardmentioning
confidence: 99%
“…His mass-frequency histograms were difficult to interpret because the late Downloaded by [Universite Laval] at 03:09 26 December 2014 instar female larvae were 2-3 times the mass of male larvae yet were only 6-8 mm longer. Body weight measurements are useful for physiological studies on stoneflies (Branham & Hathaway 1975); however, we have found it more meaningful to study insect life cycles based on morphological measurements.…”
Section: Introductionmentioning
confidence: 99%